2021
DOI: 10.1038/s41598-021-97758-7
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine ameliorates depressive-like behaviors in mice through increasing glucose uptake regulated by the ERK/GLUT3 signaling pathway

Abstract: To investigate the effects of ketamine on glucose uptake and glucose transporter (GLUT) expression in depressive-like mice. After HA1800 cells were treated with ketamine, 2-[N-(7-Nitrobenz-2-oxa-1,3-diazol-4-yl)Amino]-2-Deoxyglucose (2-NBDG) was added to the cells to test the effects of ketamine on glucose uptake, production of lactate, and expression levels of GLUT, ERK1/2, AKT, and AMPK. Adult female C57BL/6 mice were subjected to chronic unpredictable mild stress (CUMS), 27 CUMS mice were randomly divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…We indeed observed that the hippocampal HO-1/CO system is involved in the depressive-like state of the animals, and CO-RM-3 administration can reverse the depressive-like symptoms. CO is known for its neuroprotective effects in the cortical amygdala and hippocampal neurons ( Hettiarachchi et al, 2014 ; Wang et al, 2017 ; Riego et al, 2018 ); the brain regions are involved in depression ( Sheline et al, 2002 ; Whalen et al, 2002 ; Liu et al, 2017b ; Seo et al, 2017 ; Du Preez et al, 2021 ; Garro-Martinez et al, 2021 ; Li et al, 2021 ; Ouyang et al, 2021 ; Qin et al, 2021 ; Sindermann et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We indeed observed that the hippocampal HO-1/CO system is involved in the depressive-like state of the animals, and CO-RM-3 administration can reverse the depressive-like symptoms. CO is known for its neuroprotective effects in the cortical amygdala and hippocampal neurons ( Hettiarachchi et al, 2014 ; Wang et al, 2017 ; Riego et al, 2018 ); the brain regions are involved in depression ( Sheline et al, 2002 ; Whalen et al, 2002 ; Liu et al, 2017b ; Seo et al, 2017 ; Du Preez et al, 2021 ; Garro-Martinez et al, 2021 ; Li et al, 2021 ; Ouyang et al, 2021 ; Qin et al, 2021 ; Sindermann et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the kynurenine pathway has been reported to play a key role. At present, the pharmacological treatment of major depression is often suboptimal and associated with substantial side effects [ 9 12 ]. Therefore, it is essential to identify the exact mechanisms of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the prefrontal cortex, this expression was modulated by the estrous cycle [61]. The administration of ketamine in female mice exposed to chronic unpredictable mild stress was reported to be mediated via the extracellular-signal-regulated kinase and glucose transporter 3 (ERK/GLUT3) signaling pathway [62].…”
Section: Ketamine Sexually Dimorphic Antidepressant Effectsmentioning
confidence: 99%